A PRAGMATICS ANALYSIS OF ILLOCUTIONARY ACTS IN MICHELLE OBAMA’S SPEECHES - Nurhalizah, A. Siti Madya; Sili, Surya; Asanti, Chris (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
This research is aimed to find the classification of illocutionary acts, and the way it is conveyed by Michelle Obama in delivering her political campaign speeches in supporting Hillary Clinton and Tim Kaine in United States presidential election in 2016. The researcher used qualitative analysis approach in analyzing and interpreting the data. The data source of this research was Michelle Obama’s political campaign speeches that were held in Manchester, New Hampshire on October 13, 2016 and in Phoenix on October 20, 2016. Through the finding of the analysis, there were 267 data of illocutionary acts. They are divided into four types, namely representatives, directives, commissives, and expressives. And from all the data of illocutionary acts found in the speeches, there were 230 data conveyed in direct way and there were 37 data conveyed in indirect way.